Animacy, agentivity, and the spread of the progressive in Modern English - Hundt, Marianne (English language and linguistics, 2004)
One aspect of the grammaticalization of the progressive is its spread in Modern English. Previous studies suggest that the progressive was initially restricted to animate or agentive subjects and spread to inanimate or nonagentive subjects only during the later stages of grammaticalization in Modern English. The article discusses the contextual variables - animacy and agentivity - that have been used in previous research. ARCHER - A Representative Corpus of Historical English Registers - is then used (a) to verify the hypothesis that progressives increasingly co-occur with inanimate/nonagentive subjects in the eighteenth and nineteenth centuries, (b) to test the reliability and comparability of previous research, (c) to verify whether the weakening of the contextual constraint was a condition for or a result of the spread of the progressive form in the nineteenth century, and (d) to find out whether there are any regional differences between American and British English in the loss of the contextual constraint.